Extracorporeal shockwave therapy in managing lower urinary tract dysfunction: a scoping review - Handayani, Yoshimi; Yufika, Amanda; Lestari, Lazulfa Inda; Setiono, Steven (Faculty of Medicine Universitas Indonesia, 2025)
Extracorporeal shockwave therapy (ESWT) exerts a range of biological effects, including anti-inflammatory, immunomodulatory, angiogenic, proliferative, and differential responses, as well as promoting nerve regeneration, enhancing membrane permeability, inducing stem cell attraction, and triggering the release of exosomes. It facilitates both interstitial and extracellular responses that support tissue regeneration by transferring energy into tissues. It may also reduce pain through hyperstimulation analgesia and attenuate inflammatory responses, making it a promising non invasive approach for various lower urinary tract dysfunction (LUTD) conditions, such as underactive bladder, overactive bladder, chronic pelvic pain syndrome, stress urinary incontinence, and interstitial cystitis. This study aimed to explore the efficacy and mechanisms of ESWT in managing LUTD.